The Wear Treatment by Nd:YAG Laser on Ti—6Al—4V Alloy: Effect of the Spot Size on Laser Beam and Seam Morphology - Gursel, A. (Металлофизика и новейшие технологии, 2015)
Due to the excellent corrosion resistance, high strength to weight ratio and high operating temperature, titanium and titanium alloys lead to successful application in various fields including the medical and aerospace industries. Among the reliable treatments techniques, laser weld can provide a significant benefit for the titanium alloys because of its precision, rapid processing capability and controlling the parameters with their effects. The Nd:YAG laser parameters, such as spot size and shape, pulse energy and duration, travel speed, peak power and frequency of repetition, influence directly or synergistically the quality of pulsed seam welds and their morphology. In this study, 1.5 mm thick titanium Ti6Al4V alloy sheet surfaces are treated by SigmaLaser®300 type Nd:YAG pulsed laser. The influence of spot size on seam morphology and effects to the surface are investigated. The seam and surface quality is characterized in terms of weld morphology and microhardness.